2015
DOI: 10.3846/btp.2015.563
|View full text |Cite
|
Sign up to set email alerts
|

Market orientation vs. inovativeness of SMEs of Podlaskie province

Abstract: This research aims to examine the impact of marketing orientation on the innovation level among Small and Medium Size (SMEs) from Podlaskie Province. A survey utilizing a questionnaire was conducted among 137 companies in the Podlaskie Voivodeship. Altogether 3 hypotheses concerning marketing orientation and innovativeness level have been examined with the use of the hierarchical regression techniques. The relation between three types of marketing orientation and innovativeness has been analysed: customer orie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…The result of the regression analysis showed that inter-functional coordination has no significant impact on SME innovativeness. This finding supports the results obtained by Ejdys (2015), which affirmed the lack of a positive effect of the inter-functional coordination on innovativeness. The rationale behind the obtained results may be because many SMEs are not well organized in Yemen.…”
Section: Impact Of Market Orientation On Innovativenesssupporting
confidence: 91%
“…The result of the regression analysis showed that inter-functional coordination has no significant impact on SME innovativeness. This finding supports the results obtained by Ejdys (2015), which affirmed the lack of a positive effect of the inter-functional coordination on innovativeness. The rationale behind the obtained results may be because many SMEs are not well organized in Yemen.…”
Section: Impact Of Market Orientation On Innovativenesssupporting
confidence: 91%
“…The acceptance of our proposed hypothesis provides several conclusions in managing market orientation for enhancing marketing performance. Firstly, strengthening the R-A Theory-based on the study of Ejdys (2015), de Guimarães et al (2018), and(Le et al, 2018) that recognizing market orientation as a strategic asset or strategic driver for enhancing marketing performance. This strategic driver is proved as an effective tool for enhancing the technoresonance innovation capability which strengthening the study of innovation capability (Adam et al, 2014;Chung, 2019;De Guimarães, Severo, Campos, El-Aouar, & Azevedo, 2019;Huhtala et al, 2014;Sullaida et al, 2018) as a strategic leverage for enhancing marketing performance.…”
Section: Research Conclusionmentioning
confidence: 99%
“…There is a clear shift of focus from long-term customer relationships (Kohli & Jaworski, 1990) to the delivery of new values, and this is directly related to development and innovation (e.g. Deschamps, 2008;Ejdys, 2015;Foley, 2004;Gallarza & Gil-Saura, 2011, Saarijarvi et al, 2015Pomffyova et al, 2016). Thus, discussions regarding customer orientation are impossible without innovation, and these categories depend on the decision of the leader (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…As individual cognitive categories, they are a common subject of study with customer orientation continually evolving mainly due to the dynamic changes within the business environment. Assuming the perspective of an organisation, customer orientation is a part of market orientation (Ejdys, 2015). It consists of a company treating a customer as a source of inspiration as well as the final judge in the process of the market offer development, which results in a favourable attitude of the customer towards the company and enables the company to retain the customer, thus benefiting both parties (Mazurek-Lopacinska, 2011).…”
Section: Introductionmentioning
confidence: 99%